Pregnancy upregulates angiotensin type 2 receptor expression and increases blood flow in uterine arteries of rats. Issue 5 (1st June 2018) - Mishra, Jay S; Gopalakrishnan, Kathirvel; Kumar, Sathish
Abstract: Normal pregnancy is associated with decreased uterine vascular contraction and increased blood flow even though angiotensin II (AngII) levels are increased. AngII not only activates the angiotensin type 1 receptor (AT1 R) to mediate vasoconstriction but also angiotensin type 2 receptor (AT2 R) to cause vasodilation. We hypothesized that upregulation of AT2 R expression and function accounts for increased uterine artery blood flow during pregnancy. Virgin, pregnant (at different days of gestation) and post-partum Sprague-Dawley rats were used to determine uterine artery hemodynamics using micro ultrasound and plasma angiotensin II levels by ELISA. Isolated uterine arteries were examined for AT1 R and AT2 R expression and isometric contraction/relaxation. Plasma AngII levels were steady up to mid-pregnancy, increased as pregnancy advanced, reaching a peak in late pregnancy, and then restored to pre-pregnant levels after delivery. The pattern of increase in AngII levels mirrored a parallel increase in uterine blood flow. AT1 R expression did not change, but AT2 R expression increased during pregnancy correlating with uterine blood flow increase. Treatment with the AT2 R antagonist PD123319 reduced uterine arterial blood flow. Vasoconstriction to angiotensin II was blunted in pregnant rats. Treatment with PD123319 caused greater enhancement of AngII contraction in pregnant than virgin rats. Ex vivo exposure of estradiol to uterine arterial rings dose dependently upregulated AT2 R expression, that was inhibited by estrogen receptor antagonist. These results demonstrate that elevated AngII levels during gestation induce an increase in uterine blood flow via heightened AT2 R-mediated signaling. Estrogens appear to directly upregulate uterine vascular AT2 R independent of any endogenous factors. Abstract : Elevated angiotensin II induces an increase in uterine arterial blood flow in pregnant rats via heightened angiotensin II type 2 receptor-mediated signaling, providing a molecular mechanism linking renin-angiotensin system and gestational adaptations.